HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP IBU TERHADAP PERILAKU PENGGUNAAN KONTRASESPSI KB DI PUSKESMAS SIKO KECAMATAN KOTA TERNATE UTARA TAHUN 2013 - Astri, Hetty; Alhadar, Farida (Jurnal Kesehatan Poltekkes Ternate, 2014)
Abstract : The high rate of maternal mortality in Indonesia prompted the government to re-optimize the Family Planning . There are several factors that influence a person's behavior, two of which are knowledge and attitude. Factors to be observed in this study, which aims to determine the relationship of mother's level of knowledge and attitude towards the behavior of the use of contraception in the health center district of Siko in 2013. Design research is a descriptive cross-sectional study with a sample size of 49 people with accidential sampling. The analysis used in this research is using chi square analysis (X2). Instrumen in this study was a questionnaire that includes the data of respondents, questionnaires knowledge, attitudes, and behaviors. The results were obtained an average of 12.18 knowledge, median 12.00, with a standard deviation of 2.369. Respondents who have a good knowledge of as much as 16%, just 61%, less than 22%. Knowledge is lowest at the highest 8 17. While the average maternal attitude is 8.33, median 9.0 with a standard deviation 1.329. The number of respondents who have a negative attitude is 49% and that 51% have a positive attitude. The minimum value of 5 attitudes and values maksmimum attitude is 11. To obtain the behavior of the average value of 0.73, the median standard deviation of 1.00 and 0.446. The number of respondents who behave using birth control as much as 73.5% and were not as much as 26.5%. Based on the results obtained by statistical tests where X2 (3.560) is smaller than X2 table (11.07). This shows a lack of correlation between knowledge and attitude toward the behavior, in other words, a high level of knowledge and a positive attitude does not mean behaviour be positive. From the results of this study are expected to examine other factors that relate more to the behavior that family planning programs launched by the government can be optimized, effective and efficient.